Mapping archaeometallurgical data of the Iberian Copper Age: Different ways to look at a big picture. (July 2020) - Perucchetti, L.; Montero-Ruiz, I.; Bray, P.
Abstract: Traditionally, archaeometallurgical projects have visualised information through distribution maps of the find spots for different metal compositions or types of objects. However, this is limiting, and more innovative styles of communication are required to engage with more dynamic technological questions such as what underpins the use and circulation of metal. This paper compares four ways to process and represent the archaeometallurgical chemical composition dataset for Copper Age Iberia, and the different conclusions they tend to support. Using distribution maps, the wide spread of arsenical copper is clear, however more nuanced features are obscured. Through employing ubiquity analysis, with regular or irregular grids, it is possible to understand the relative importance of arsenical copper within the local consumption of metal, and how this relates to local extraction. While Relative Risk maps can suggest links between metal circulation and geographical features, particularly rivers. Rather than just being an aesthetic concern, we aim to demonstrate that visualisation of georeferenced data is an important research method. Graphical abstract: Image 1 Highlights: It is thought that most of the metal in the Iberian Copper Age was locally extracted and consumed. In the Copper Age Iberian Peninsula, there was a widespread of arsenical copper. The use and circulation of metal is clearer using different ways to visualise geographical analytical. Data visualisation is not an aesthetic concern, but an active instrument of research.